Effect of moxidectin on CYP3A4 activity as evaluated by oral midazolam pharmacokinetics in healthy subjects. Issue 2 (22nd October 2013) - Korth‐Bradley, Joan M.; Parks, Virginia; Wagner, Frank; Chalon, Stephan; Gourley, Ian; Matschke, Kyle; Gossart, Sophie; Ripp, Sharon L.; Fleckenstein, Lawrence
Abstract In order to evaluate the potential for CYP3A4 induction by moxidectin, midazolam pharmacokinetic (PK) parameters were compared before and after moxidectin administration. Healthy subjects received a single 8 mg dose of moxidectin and 3 single 7.5 mg doses of midazolam 3 days before, and 7 and 89 days after the moxidectin. Blood samples were taken for 24 hours to measure midazolam and metabolites in plasma, and for 89 days to measure moxidectin in plasma after dose administration. Noncompartmental PK analyses were performed for each analyte. Analysis of variance was performed on log‐transformed midazolam parameters with treatment day as a fixed effect. Adverse events were recorded and laboratory tests, physical examinations, pulse oximetry monitoring, vital sign measurement, and electrocardiograms performed. Thirty‐nine subjects were enrolled in the study; PK data were available for 37 subjects. Moxidectin PK parameters were similar to previous studies. There were no significant changes in PK for midazolam or its metabolites 7 or 89 days after moxidectin administration. Adverse events were generally mild and there were no relevant changes in safety assessments. Thus, 8 mg moxidectin does not induce CYP3A4 activity and other CYP3A4 substrates are unlikely to be affected by moxidectin co‐administration.